2008
DOI: 10.1128/cvi.00344-07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipopolysaccharide andMannheimia haemolyticaLeukotoxin on Bovine Lung Microvascular Endothelial Cells and Alveolar Epithelial Cells

Abstract: Bovine respiratory disease resulting from infection with Mannheimia haemolytica commonly results in extensive vascular leakage into the alveoli. M. haemolytica produces two substances, lipopolysaccharide (LPS) and leukotoxin (LKT), that are known to be important in inducing some of the pathological changes. In the present study, we examined bovine pulmonary epithelial (BPE) cell and bovine lung microvascular endothelial cell monolayer permeability, as measured by trans-well endothelial and epithelial cell elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The adenovirus Bcl-x L expression vector, the GFP-nucleolin expression vector pEGF-C1 and Renilla-Bcl-x L construct were gifts of Yuichiro J. Suzuki (Georgetown University, Washington, DC), Michael Kastan (St Jude Children's Research Hospital, Memphis, TN) (Takagi et al, 2005) and George Tim Bowden (University of Arizona, Tucson, AZ) (Zhang et al, 2008), respectively. Immortalized bovine PEpCs were a gift of David McClenahan (University of Northern Iowa, Cedar Falls, IA) (McClenahan et al, 2008).…”
Section: Reagentsmentioning
confidence: 99%
“…The adenovirus Bcl-x L expression vector, the GFP-nucleolin expression vector pEGF-C1 and Renilla-Bcl-x L construct were gifts of Yuichiro J. Suzuki (Georgetown University, Washington, DC), Michael Kastan (St Jude Children's Research Hospital, Memphis, TN) (Takagi et al, 2005) and George Tim Bowden (University of Arizona, Tucson, AZ) (Zhang et al, 2008), respectively. Immortalized bovine PEpCs were a gift of David McClenahan (University of Northern Iowa, Cedar Falls, IA) (McClenahan et al, 2008).…”
Section: Reagentsmentioning
confidence: 99%
“…We have previously demonstrated that lipopolysaccharide (LPS) can induce permeability changes in endothelial cells in vitro that would be consistent with vascular leakage. However, the effects are slow, requiring well over 12 h to cause measurable effects on permeability (13). It is possible that the host releases substances in the early pathological response that contribute to the extensive leakage of vascular products into the lung.…”
mentioning
confidence: 99%
“…23,24 LPS is a potent vasodilator; it stimulates pulmonary endothelial changes consistent with the vascular leakage. 86 In addition, when administered intravenously in sheep, LPS produces clinical signs associated with the hypotension. 4 The systemic effects of LPS are considerably important in acute pasteurellosis, which causes septicemia in lambs, resulting in high mortality.…”
mentioning
confidence: 99%